Comparison of fusion of different algorithms in mapping of Melaleuca forest in Marang district, Malaysia - Saberioon, Mohammadmehdi; Mardan, Makhdzir; Nordin, Laili; Mohd Sood, Alias (Universiti Putra Malaysia Press, 2011)
Melaleuca cajuputi and Acacia auriculiformis trees are major sources of nectar and pollen for Apis dorsata and the colonies are a major source of honey to the rural poor, honey hunters. Honey is a supplementary income to many of these people (including school children) in the Marang district, Terengganu. In this study, Marang area with 270 square kilometers was chosen as pilot study area in Terengganu state for mapping M. cajuputi and A. auriculiformis as two dominant species in low land secondary forest in Terengganu state. To inventory and produce land use map of Melaleuca forest in Marang area, in this study SPOT-5 satellite image in multispectral mode with 10 meter resolution which is acquired in 2007 as optical satellite was utilized. Most images from optical satellites have some null data from ground because of clouds and shadow of clouds. To solve this problem, Hue, Saturation and value (HSV) and Principal Component Analysis (PCA) were used as fusion techniques to replace null data with microwave data which taken from Radarsat-1 image in C-band with 25 meter resolution image. Accordingly, fusion technique which was used in this research not only was a technique to improve information but also caused the accuracy increasing than land use map by just only SPOT-5 image. Also between two different fusion techniques, PCA shows the better result than HSV as two different fusion techniques.